Changes in homestead biodiversity with modernization in the rural areas of Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2017)
A study was carried out at selected villages in Gazipur district of Bangladesh during 2008- 2009 with a view to assess the changes in homestead biodiversity with degree of modernization in the rural areas. Three villages were selected purposively considering their degree of modernization e.g. traditional, semi-modern and modern village and biodiversity at 40 randomly selected homesteads from each of the three villages were studied. Species richness, interspecies diversity (Shannon-Wiener diversity index) and species evenness were considered for measuring the biodiversity. A total of 188 plant species belonging to 75 different families were identified in the homesteads of three study villages. The highest proportion (11%) of species found under the family Gramineae followed by Cucurbitaceae (6%), Compositae (5%), Solanaceae (5%), Leguminosae (4%), Amaranthaceae (4%), Rutaceae (3%), Euphorbiaceae (3%), Convolvulaceae (3%), and Cyperaceae (3%) and so on. Among the 188 plant species, 15% fruits species, 9% timber, 11% ornamental and medicinal, 14% vegetables, 4% spices and 47% weed species. The highest number (172) of species was found in traditional village and the lowest (126) in the modern village. Diversity index (H) value for traditional village (1.652) was statistically similar to semi-modern village (1.373) but significantly higher (t = 2.47*) than that of modern village (1.029). So, it can be said that plant biodiversity is decreasing with increase in modernization and/or urbanization. The diversity (H) decreased with decrease in farm size, in other words, species diversity increased with increase in farm size but there was no significant difference among the farm categories in this regard. The total evenness values against the three villages (0.741, 0.630 and 0.491 in Bhawal Gazipur, Hatiyabo and Mariali, respectively) indicate that the abundance of different species was very dissimilar and decreased with increase in modernization.Int. J. Agril. Res. Innov. & Tech. 7 (1): 32-37, June, 2017